2020
DOI: 10.1371/journal.pone.0236742
|View full text |Cite
|
Sign up to set email alerts
|

Local anesthesia in piglets undergoing castration—A comparative study to investigate the analgesic effects of four local anesthetics on the basis of acute physiological responses and limb movements

Abstract: Surgical castration of male piglets without analgesia is a painful procedure. This prospective, randomized and double-blinded study aimed to evaluate the analgesic effects of four different local anesthetics for piglet castration during the first week of life. In total, 54 piglets aged 3 to 7 days were distributed into 6 treatment groups: handling (H); castration without pain relief (sodium chloride, NaCl); and castration with a local anesthetic: 4% procaine (P), 2% lidocaine (L), 0.5% bupivacaine (B) or 20 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 44 publications
6
27
0
Order By: Relevance
“…Studies of piglet nociceptive motor and vocal response identify traction on, and severing the spermatic cords [7,14,15] as inducing the greatest pain [7,[14][15][16]52] of the procedure. Previous studies identified pre-emptive lidocaine or bupivacaine injection as effective to mitigate the pain-induced (nociceptive) motor response [22,28,36,37]. Most recently, Saller et al [28] reported that, used in combination with light general anaesthesia to minimise the motor response to restraint and handling stress, Lidocaine 2%, Bupivacaine 0.5%, Mepivacaine 2% and Procaine administered via injection 20 min prior to castration were all effective to block the nociceptive motor response to castration as compared with those injected with normal saline (placebo).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of piglet nociceptive motor and vocal response identify traction on, and severing the spermatic cords [7,14,15] as inducing the greatest pain [7,[14][15][16]52] of the procedure. Previous studies identified pre-emptive lidocaine or bupivacaine injection as effective to mitigate the pain-induced (nociceptive) motor response [22,28,36,37]. Most recently, Saller et al [28] reported that, used in combination with light general anaesthesia to minimise the motor response to restraint and handling stress, Lidocaine 2%, Bupivacaine 0.5%, Mepivacaine 2% and Procaine administered via injection 20 min prior to castration were all effective to block the nociceptive motor response to castration as compared with those injected with normal saline (placebo).…”
Section: Discussionmentioning
confidence: 99%
“…Although reports vary [18][19][20][21], analgesics such as Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) may be of use to address inflammatory-related pain that develops in the postoperative period [8,22], but generally lack efficacy to ameliorate pain during the procedure and in the early post-operative period when pain is most acute [4,23,24]. Standard methods for addressing surgical procedural pain, such as the use of general anaesthesia [18,[25][26][27][28][29] or injected local anaesthetics, although effective to mitigate acute intra-operative pain, used alone, they provide little post-operative pain mitigation [22,24,25,28,[30][31][32][33][34][35][36][37][38][39][40]. Furthermore, their use may be impractical and/or impeded on-farm by cost, logistics, occupational health and safety, food safety or welfare concerns.…”
Section: Introductionmentioning
confidence: 99%
“…Pre-emptive use of local anaesthesia via intra-testicular (i.t.) or infundibular injection, or via topical wound instillation, has been associated with reduced cortisol levels as compared with untreated animals in some trials [24,39,44], while not in others [24,36,46,74], or only where local anaesthetics and NSAIDs have been used in combination [20]. As detailed above, the lack of efficacy of local or general anaesthesia to reduce cortisol or ACTH does not, however, represent lack of efficacy to mitigate pain.…”
Section: Physiological Measurements Of Pain In Pigletsmentioning
confidence: 99%
“…Neural markers of pain mitigation, such as the expression of the c-fos gene and its protein product, Fos, in neurons of the spinal cord [75], are significantly reduced when piglets are castrated under effective local or general anaesthesia, as compared with piglets castrated without anaesthesia [43]. Furthermore, this is associated with a dramatic reduction in the nociceptive motor and vocal response to castration [31,32,74]. Additionally, reduced postoperative hyperalgesia has been documented in local anaesthetic-treated piglets [31,32].…”
Section: Physiological Measurements Of Pain In Pigletsmentioning
confidence: 99%
See 1 more Smart Citation